Feminist Dystopia or Cautionary Tale? Unpacking America’s Reflection in The Handmaid’s Tale Movie Series Season I - Neswari, Birgitta Ardhana (Universitas Negeri Semarang, 2025)
This article explores The Handmaid’s Tale Season I as both a feminist dystopia and a cautionary tale, offering critical insights into contemporary issues of gender inequality, ideological control, and the politicization of women’s bodies. Set in the theocratic regime of Gilead, the series highlights the systemic subjugation of women and the dangers of authoritarian governance masked by religious rhetoric. The study uses a qualitative method to examine visual and narrative elements from ten purposively selected episodes, chosen for their strong thematic relevance to gendered oppression. Library research complements this analysis by providing supporting feminist theory and socio-political context. Three central themes are addressed: the politics of bodily autonomy and state control, the enforcement of patriarchal power structures, and the fusion of religion and governance as a tool of subjugation. These themes reveal strong parallels between the fictional society of Gilead and ongoing struggles in the United States, such as the rollback of reproductive rights and rising political conservatism. By examining these connections, the article not only warns against the normalization of oppression but also encourages critical awareness and public engagement. Ultimately, the series serves as a cultural mirror that can inspire societal reflection, advocacy, and concrete progress toward gender equality and human rights.